A dual channel rhodamine appended smart probe for selective recognition of Cu2+ and Hg2+ via “turn on” optical readout - Sada P.K.; Bar A.; Jassal A.K.; Singh A.K.; Singh L.; Rai A. (My University, 2025)
A new rhodamine-6G hydrazone RHMA has been synthesized using rhodamine-6G hydrazide and 5-Allyl-3-methoxysalicylaldehyde. RHMA has been fully characterized with different spectroscopic methods and single crystal XRD. RHMA can selectively recognize Cu2+ and Hg2+ in aqueous media amongst other common competitive metal ions. A significant change in absorbance was observed with Cu2+ and Hg2+ ions with emergence of a new peak at λmax 524 nm and 531 nm respectively. Hg2+ ions lead to “turn-on” fluorescence enhancement at λmax 555 nm. This event of absorbance and fluorescence marks the opening of spirolactum ring causing visual color change from colorless to magenta and light pink.RHMA-Cu2+ and RHMA- Hg2+complexes are found to be reversible in presence of EDTA2−ions. RHMA has real application in form of test strip. Additionally, the probe exhibits turn-on readout-based sequential logic gate-based monitoring of Cu2+ and Hg2+ at ppm levels, which may be able to address real-world challenges through simple synthesis, quick recovery, response in water, “by-eye” detection, reversible response, great selectivity, and a variety of output for accurate investigation. © 2023